CAUTION: on the many, unpredictable iterations of a yellow border sign ideograph and migrant/queer world-making. Issue 3 (3rd July 2019) - Andrade, Luis M.
ABSTRACT: In the late 1980s and early 1990s, artist John Hood collaborated with California's Department of Transportation to erect yellow "CAUTION" signs to warn drivers against migrants running across the San Diego freeways. This essay marries migrant/queer world-making theories and ideographic analysis to describe how artists imagined new, often contradictory, worlds to resist modernist notions of citizenship, gender, sex, family, and humanity through (re)drawn iterations of the sign. I show an overlapping and reflexive interplay between what the iterations visually represent and the ways that migrants/queers, including my familia, perform what the images mean in the realm of the material, everyday.